Pengaruh Gaya Kepemimpinan Servant Leadership terhadap Kinerja Karyawan dengan Kepuasan Kerja sebagai Variabel Intervening - Yuanita, Rizka; Padmantyo, Sri (Prosiding University Research Colloquium, 2022)
This study aims to analyze the effect of Servant leadership on employee performance through job satisfaction as an intervening variable. The population and sample of this study were private employee in Keresidenan Surakarta as many as 200 respondents. The type of data used in this research is primary data. The data collection method is using a questionnaire and processed using Partial Least Square (PLS) analysis tool. The results show that Servant leadership has a positive and significant effect on employee performance. Servant leadership has a positive and significant effect on job satisfaction. Job satisfaction has a positive and significant effect on employee performance. Servant leadership has a significant effect on employee performance which is mediated by job satisfaction. This research is intended to provide an overview of the influence of servant leadership leadership style on employee performance mediated by job satisfaction so that the results of this study are expected to assist companies in maximizing the performance of human resources carried out.